Interactive Effects of Catfish Aquaculture Effluent and NPK Fertilizer on Tomato Growth and Yield under Tropical Field Conditions - Kartika, Defi; Yuliana, Anggi Indah; Nasirudin, Mohamad (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study evaluated the individual and interactive effects of graded levels of catfish aquaculture wastewater and graded rates of nitrogen phosphorus potassium fertilizer on the growth and yield of tomato under tropical field conditions. Using a two‐factorial randomized complete block design, treatments included five volumes of wastewater and three fertilizer rates, each replicated three times. Growth parameters were assessed at multiple intervals, and fruit yield and biomass were recorded through successive harvests. The highest fertilizer rate resulted in the most vigorous early canopy development, greatest fruit weight in the initial harvests, and highest shoot biomass at maturity. Catfish wastewater alone did not enhance any measured parameter, but a modest wastewater addition combined with full fertilizer rate produced a notable improvement in early leaf expansion. These findings confirm the essential role of balanced inorganic nutrition in tomato production and identify a narrow window in which low‐level organic input can complement chemical fertilizer. Practical implications include the potential for smallholder farmers to valorize aquaculture by‐products and reduce synthetic input without compromising performance.